2004
DOI: 10.1016/j.jtcvs.2004.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The failing Fontan circulation: Successful conversion of atriopulmonary connections

Abstract: Fontan conversion can be achieved with low mortality and improvement in New York Heart Association class and exercise ability. Concomitant arrhythmia surgery reduces the incidence of late arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 11 publications
4
33
0
Order By: Relevance
“…Marcelletti et al reported that the Fontan conversion reduced the risk for arrhythmia and thrombo-embolism [7]. Especially when anti-arrhythmic surgical intervention was performed at the Fontan conversion simultaneously, this procedure decreased arrhythmia resulting in overall improvement in quality of life and functional class [8][9][10]. In our series, the improvement from 19% to 74% of NYHA class I was recognized, which could be attributed to restoration of regular rhythm.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Marcelletti et al reported that the Fontan conversion reduced the risk for arrhythmia and thrombo-embolism [7]. Especially when anti-arrhythmic surgical intervention was performed at the Fontan conversion simultaneously, this procedure decreased arrhythmia resulting in overall improvement in quality of life and functional class [8][9][10]. In our series, the improvement from 19% to 74% of NYHA class I was recognized, which could be attributed to restoration of regular rhythm.…”
Section: Discussionsupporting
confidence: 52%
“…Atrial arrhythmia was also one of the important factors to decide the postoperative quality of life. Recently, Fontan conversion and thrombus removal with concomitant arrhythmia surgery and pacemaker placement were performed for the patients who had dilated right atrium, large thrombus in the right atrium and atrial tachyarrhythmia after Fontan completion [6][7][8][9]. Fontan conversion has been performed to rescue the failed Fontan circulation as a palliative strategy [10], and its indication for Fontan conversion is still controversial and surgical outcomes are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, such patients have improved hemodynamics and increased cardiac output after a revision. 53 This technique has been successfully applied in the patient after atrio-pulmonary Fontan operation that has atrial arrhythmias and thrombembolic disease. 54 Another intense form of therapy for a patient with PLE after Fontan operation is heart transplantation, in which the objective is to completely normalize hemodynamics by replacing the single ventricle Fontan construct with a 2-ventricle system.…”
Section: Suggested Treatment Strategies For Ple After Fontan Operationmentioning
confidence: 99%
“…1 The management of these patients is extremely difficult, because the origin of their poor clinical status may be multifactorial. 2 We present a case of a young adult with a failing Fontan circulation who went into intractable heart failure after reoperation and was finally rescued by left ventricular assist device (LVAD) implantation as a bridge to orthotopic heart transplant.…”
mentioning
confidence: 99%